DIFFICULTIES IN RENDERING ENGLISH POLYSEMANTIC WORDS - Ochilova Nafisa Usmanovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
One of the difficulties that make language teachers think carefully about the introduction of words with their different meanings and phraseological units of the foreign language. Every language is made bright and colorful with its idioms, phrases and wide range of the usage of words with their different meanings. It is helpful for a native speaker to express their thoughts; on the other hand it is hard for a foreign language learner to understand them correctly.